2017
DOI: 10.1002/ceat.201600712
|View full text |Cite
|
Sign up to set email alerts
|

Chemical‐Free Pest Control by Dielectric Heating with Radio Waves and Microwaves: Thermal Effects

Abstract: Thermal pest control with hot air is widely accepted as an alternative to chemical methods. However, it requires relatively long treatment times owing to the low thermal conductivity of wood. Direct dielectric heating that applies radio waves or microwaves has the advantage of more homogeneous heating. However, sound experimental data on this technique are currently rare. Therefore, the thermal treatment of wood-destroying insects with radio waves and microwaves was studied with two model pests, Anobium puncta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…During the last decade, several studies have supported the efficiency of microwave heating of wood [18][19][20][21][22][23][24][25] and wood-invading insects 7,10,11,26 . However, some other studies reported reduced or no lethal impact on pests 24,27,28 . According to Nakai et al 27 , direct exposure of the termite body to microwave radiation did not show a lethal effect.…”
mentioning
confidence: 99%
“…During the last decade, several studies have supported the efficiency of microwave heating of wood [18][19][20][21][22][23][24][25] and wood-invading insects 7,10,11,26 . However, some other studies reported reduced or no lethal impact on pests 24,27,28 . According to Nakai et al 27 , direct exposure of the termite body to microwave radiation did not show a lethal effect.…”
mentioning
confidence: 99%
“…Mortality tests were carried out analogously to the studies described in previous papers , with mealworm beetle larvae as a reference for wood‐destroying pests.…”
Section: Methodsmentioning
confidence: 58%
“…For the RF heating experiments, a similar generator system to that employed for the tests described in a previous publication and elsewhere was used (fixed working frequency of 13.56 MHz, PFG 1000 RF generator with matching network PFM 3000A, both water‐cooled, from Trumpf Hüttinger, Freiburg/Brsg., Germany). The RF voltage was measured with a high‐voltage probe (P6015A, from Tektronix Inc., Plano, USA) in combination with a potential divider (1:1000) and an oscilloscope (RTO 1024, 2 GHz, 10 GSa s −1 , Rohde & Schwarz, Neu‐Isenburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations